Promoting language creativity by using Internet and scamper among primary five pupils - Dianaros Ab Majid (2008)
The purpose of this study is to examine the effect of the use of Internet and SCAMPER in the promotion of language creativity among Primary Five pupils between the age of ten and eleven years old.